What Is a "Good" Estimate? - Armour, Phillip G. (Communications of the ACM, 2013)
The author discusses the development of estimates in software project management. He argues that like an effective weather forecast, a software project estimate should also incorporate factors such as accuracy, consistency, quality, value, honesty, and return. Topics include data inclusion requirements, probability of correspondence between estimate and result, and recalibration of estimates for future projects.